An opinion survey of Delay in Road Construction in City Area and its effects - Nepal, Pramshu (The Lumbini Journal of Business and Economics, 2024)
Purpose: This study aims to investigate the causes and effects of delays in road construction across various areas in Nepal. Its objective is to identify the key factors contributing to these delays and examine how they affect different stakeholders, including the general public, businesses, and the government. Method: This research used a mixed-method approach, combining a questionnaire survey with Focus Group Discussions (FGDs) to gather comprehensive data on road construction delays. Key stakeholders, particularly those impacted by road construction projects, were surveyed to collect their views on the causes of delays and the resulting consequences. Results: There is identified several major factors causing delays in road construction projects in Nepal including frequent government changes, alterations in project design, low labor productivity, inadequate planning, political interference and protection, and a shortage of resources. Conclusion: The study concludes that delays in road construction projects not only increase costs but also diminish public trust, growing public dissatisfaction. Stakeholders expressed frustration with the slow pace of construction, emphasizing its adverse effects on businesses, public health, and road safety.